Resistivity Model of Clayshale Layers in Dry Season and Early Rainy Season Conditions Case Study of the Jragung Dam Project - Sasangka, Daru Jaka; Arisanto, Pranu; Dhanardono, Bhima; Riyanto, Didit Puji; Apriyoga, Wahyu (Bentang : Jurnal Teoritis dan Terapan Bidang Rekayasa Sipil, 2024)
The use of geoelectricity as subsurface data acquisition will be very helpful if used to perform correlations on rock formations. The aim of this research is to look at the pattern of subsurface resistivity values ​​compared to the condition of rock layers or outcrops in the field. The geoelectric survey used the dipole dipole method with the Multichannel Resistivity MAE X 612 EM+ instrument. The case study was carried out at one of the excavation locations at Jragung Dam with sandstone and clay stone lithology with varying thicknesses. Conditions in the field are that the clay stone layer is starting to experience greater deformation compared to the sandstone layer. Worse deformation in claystone in the field is caused by durability values ​​which are generally worse than sandstone and the greater water content in claystone even though its compressive strength is relatively greater. In the dry season, sandstone (Reference point 1) at a depth of 5m has a resistivity of >86 ohm.m, while claystone has 12 - 15 ohm.m. At the beginning of the rainy season sandstone 37 – 50 ohm.m, clay stone (reference point 1) resistivity 8-11 ohm.m. The resistivity of claystone does not change significantly with changes in conditions. Because the porosity and permeability of sandstone can change significantly under changing